Contribution of advanced neuroimaging in diagnosis of cerebral syphilitic gumma: a case report - Shen, Xinyi; Zhu, Zhengyang; Li, Xin; Zhang, Wen; Zhang, Xin; Zhang, Bing (Frontiers in Neuroscience, 2024)
Background Cerebral syphilitic gumma is a rare intracranial infectious disorder. Without a clear history of syphilis and comprehensive serological examinations, it’s challenging to diagnose it accurately prior to surgery through routine magnetic resonance imaging (MRI). Advanced neuroimaging techniques have been widely used in diagnosing brain tumors, yet there’s limited report on their application in cerebral syphilitic gumma. This report presents a case of an elderly male patient with cerebral syphilitic gumma and analyzes its characteristics of advanced neuroimaging. Case presentation A 68-year-old male patient was admitted to our institution presenting with bilateral hearing loss complicated with continuing headaches without obvious cause. Laboratory tests indicated positive treponema pallidum. Conventional MRI showed nodules closely related to the adjacent meninges in bilateral temporal lobes. The patient underwent surgical resection of the nodule in the right temporal lobe due to the mass effect and the final pathological diagnosis revealed cerebral syphilitic gumma. Conclusions With the return of syphilis in recent years, accurate diagnosis of cerebral syphilitic gumma is a matter of great urgency. Advanced neuro-MRI can serve as a significant complement to conventional MRI examination.